Risk factors for incident asthma and COPD in a cohort of young adults. (29th March 2017) - Traulsen, Lisbet Krogh; Bælum, Jesper; Halling, Anders; Thomsen, Gert; Thilsing, Trine; Sherson, David; Sigsgaard, Torben; Omland, Øyvind; Malling, Tine; Skadhauge, Lars Rauff
Abstract: Introduction: The aim of the study was to describe potential shared risk factors for incident asthma and COPD in a population‐based, 9‐year follow‐up study. Methods: From a cohort of 1191 individuals, aged 20‐44, who participated in baseline survey including spirometry, bronchial challenge, and skin prick test (SPT) 742 subjects (62%) were reexamined at follow‐up in 2012‐2014. Results: A total of 27 incident cases of asthma and 22 cases of COPD were identified at follow‐up corresponding to an incidence rate of 5.8 (95% CI 3.9‐8.4) and 3.5 (2.2‐5.3) per 1000 person years, respectively. Among the identified COPD cases a total of 12 were Asthma‐COPD Overlap Syndrome (ACOS). Atopy defined by positive SPT was a risk factor for asthma in males (OR 7.54; 95% CI 1.24‐45.90), whereas risk factors in females were nasal allergy (3.81; 1.20‐12.11), FEV1 <100% predicted (3.96; 1.07‐14.62) and parental asthma (3.06; 1.00‐9.40). Risk factors for COPD in males were bronchial hyperresponsiveness (23.13; 1.41‐380.50) and FEV1 <100% predicted (all male cases had FEV1 <100% predicted) and in females current smoking (3.34; 1.16‐9.59) and asthma at baseline (5.21; 1.48‐18.34). Conclusions: No shared risk factors for incident asthma and COPD were found. Despite low power when stratifying by sex risk factors for incident asthma and COPD emphasize considerable gender differences.